DROUGHT STRESS Improving Drought Tolerance by Exogenous Application of Glycinebetaine and Salicylic Acid in Sunflower - Hussain, M.; Malik, M. A.; Farooq, M.; Ashraf, M. Y.; Cheema, M. A.
Water shortage is a severe threat to the sustainability of crop production. Exogenous application of glycinebetaine (GB)and salicylic acid (SA)has been found very effective in reducing the adverse affects of drought stress. This study was conducted to examine the possible role of exogenous GB and SA application in improving the yield of hybrid sunflower (Helianthus annuus L.)under different irrigation regimes. There were three levels of irrigation, viz. control (normal irrigations), water stress at vegetative stage (irrigation missing at vegetative stage)and water stress at flowering stage (irrigation missing at flowering stage). GB and SA were applied exogenously at 100 and 0.724 mm, respectively, each at the vegetative and at the flowering stage. Control plants did not receive application of GB and SA. Water stress reduced the head diameter, number of achene, 1000-achene weight, achene yield and oil yield. Nevertheless, exogenous GB and SA application significantly improved these attributes under water stress. However, drought stress increased the free leaf proline and GB, and were further increased by exogenous application of GB and SA. However, exogenous GB application at the flowering stage was more effective than other treatments. Oil contents were also reduced under water stress; however, GB and SA application could not ameliorate the negative effect of water stress on achene oil contents. The effects of water stress and foliar application of GB were more pronounced when applied at the flowering stage than at the vegetative stage.
Keywords: EXOGENOUS APPLICATION; GLYCINEBETAINE; SALICYLIC ACID; DROUGHT; SUNFLOWER; PROLINE; YIELD